Christian Symbol and Ritual An Introduction - Cooke, Bernard J.; Macy, Gary (New York Oxford University Press, 2005)
Books on Christian ritual and the sacraments tend to presuppose an acquaintance with Roman Catholic thought and practice. However, even at Catholic institutions, students can lack the basic knowledge. The authors of this title aim to offer an introduction to the subject.
Keywords: Liturgics. Ritual. Christian art and symbolism. Theology, Doctrinal. RELIGION -- Institutions & Organizations. RELIGION -- Christian Rituals & Practice -- Worship & Liturgy